Effects of storage conditions on forensic examinations of blood samples and bloodstains stored for 20 years. (January 2016) - Hara, M.; Nakanishi, H.; Yoneyama, K.; Saito, K.; Takada, A.
Graphical abstract: Highlights: Bloodstain stored at below −20 °C was suitable for detecting mRNA. Even if blood was stored at below −20 °C, it wasn't suitable for detecting mRNA. Bloodstain stored at below −20 °C was suitable for STR typing. Abstract: The effects of various storage conditions on blood identification tests, DNA degradation, and short tandem repeat (STR) typing were evaluated. Bloodstains stored at room temperature, 4 °C, −20 °C, and −80 °C for 20 years; blood samples stored at −20 °C and −80 °C for 20 years; and fresh blood samples were analyzed. Leuco-malachite-green testing, anti-human hemoglobin (Hb) testing (using immunochromatography), and tests for hemoglobin-beta (HBB) mRNA were performed as blood identification tests. DNA degradation was evaluated by quantifying the ratios of 305 and 129 base pair (bp) fragments to 41 bp fragments. STR typing was performed using an AmpFlSTR® Identifiler™ Plus PCR Amplification Kit. All samples were positive in leuco-malachite-green staining and anti-human Hb assays. HBB was not detected in blood samples stored at −20 °C or −80 °C, although this marker was detected in all bloodstains. As indicated by the ratio of 129:41 bp and 305:41 bp DNA fragments, DNA from bloodstains stored at room temperature or 4 °C were significantly degraded compared to DNA from all other samples. STR typing analyses revealed that a portion of the loci was undetected in bloodstains stored at room temperature. Therefore, to prevent DNA degradation during long-term storage, it is recommended that bloodstains and blood be stored at below −20 °C. In addition, because bloodstains are more suitable for detection of blood-specific mRNAs than blood sample, it is desirable that blood is stored as bloodstain for this method.